UNDERSTANDING GRECO-ROMAN DERIVATIVES: AN IMPLICATION FOR LEARNING ANGLICIZED CONCEPTS - Muhammmad Muhammad Suleiman; Shitu Sani; Shettima Mamman Adam (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2020)
Education, in its true sense, is not synonymous with literacy, as it is very much linked to the gathering of information and to the application of effective solutions to the myriad problems of global society. The nuanced nature of the study of science in particular and humanities in general requires a great deal of effort from students, ranging from practical, field trips, excursions, records to the comprehension of derivatives and the technical sense of terms used in various fields of study, with particular reference to the unique nature of Greco-Roman words, which are typically subject to rotation by students. This gulf culminates in the student's acquisition of a lower level of learning and the deprivation of the reflective level of thought that contemporary society requires. In this paper, an attempt has been made to analyze the root derivatives of a variety of concepts and their technical interpretations, as applied in a number of different disciplines of science and humanities, in order to promote a deeper understanding of the definitions of technical words.